Assessment of microbiological hazards along the milk value chain in Kilosa and Mvomero districts, Tanzania - Joseph, E. (Sokoine University of Agriculture, 2015)
The consumption of raw milk is a common practice among pastoral and agro-pastoral communities of Tanzania. This behaviour predisposes consumers to the risk of contracting milk-borne and zoonotic diseases. This study was carried out to assess milk quality based on identification of bacterial contaminants indicated by total viable count (TVC), total coliform count (TCC) and contamination with Brucella and E. coli O157: H7 microorganisms. The study was carried out along the milk value chain (MVC) in Kilosa and Mvomero Districts of Morogoro Region in Tanzania. A total of 109 milk samples were collected along the MVC from farmers (54), milk vendors (31), milk collection centres (6) and milk selling points (18). Collected milk samples were subjected to TVC, TCC and polymerase chain reaction (PCR) to identify the presence of microorganisms in the milk. Laboratory findings indicate that milk from Kilosa district had significantly (p=0.015) higher TVC than milk from Mvomero district. The TVC varied significantly (p=0.00) along the MVC in the two districts. Using PCR, the overall prevalence of Brucella was 17.1% (n=82 out of 109), with the prevalence of 25.8% and 11.8% recorded in Kilosa and Mvomero districts, respectively. The E. coli O157:H7 was neither isolated nor detected in all 109 milk samples processed. Such findings suggest that milk marketed along the MVC is contaminated with Brucella organisms, thus posing public health risks to consumers. It is recommended that concerted efforts should be made to safeguard health of consumers through adopting various interventions that would reduce risks at each node along the MVC in the study area.